Helix rim advancement for reconstruction of marginal defects of the pinna - A. Majumdar,* J. Townend (Blackwell Synergy, 2000)
Acquired helical rim defects of the pinna are eyecatching and cosmetically unacceptable to the patient. They are usually the result of injury or local excision of a neoplasm, the most common malignant lesions being squamous cell carcinoma (SCC) or basal cell carcinoma (BCC).1 In a series of 152 SCCs of the pinna, 95 (62%) arose from the helix.2 Thomas and Mathews3 found 46% of SCCs on the helix in their series and a similar percentage was reported by Leferink and Nicolai